NIR-triggered dual sensitization of nanoparticles for mild tumor phototherapy. (February 2022) - Liu, Chang; Li, Shuolin; Ma, Ruihao; Ji, Chendong; Müllen, Klaus; Yin, Meizhen
Highlights: The NIR absorbing perylene monoimide core enables combined photothermal and photodynamic effect. The spatiotemporally controlled released inhibitors strengthened both PTT and PDT. Dual-sensitized process promoted phototherapeutic nanoparticles (NP2) accomplishing mild tumor phototherapy. Graphical Abstract: ga1 Abstract: Mild phototherapy with heat shock protein 90 (HSP90) inhibitors can be employed for tumor therapy, but suffers from non-exhaustive therapeutic effects and uncontrollable release. Herein, we present NIR-responsive and dual sensitized nanoparticles for mild tumor phototherapy. These nanoparticles were based on two perylene monoimide and a diamino anthraquinone (2PMI-AQ) chromophore as an inner hydrophobic core. To explore the sensitized function, 2PMI-AQ was modified with hydrophilic thermosensitive polymers, resulting in stable nanoparticles (NP1) via spontaneous self-assembly. The as-prepared NP1 possess a robust nanostructure and enable combined photothermal therapy (PTT) and photodynamic therapy (PDT). Besides, outside thermosensitive polymers of NP1 allow loading and photothermal release of HSP90 inhibitors. Under NIR laser irradiation, photothermal/photodynamic effects and photothermally controlled release of HSP90 inhibitors are realized simultaneously. The inhibitors inactivate the cell guardian protein HSP90 to attenuate the cytoprotection, which enhances both PTT and PDT. We thus achieve mild tumor phototherapy in vivo by using NIR-absorbing nanoparticles with dual sensitized function induced by low-power irradiation.